Controlled experiments support the role of function in the evolution of the North American copper tool repertoire. (August 2019) - Bebber, Michelle R.; Norris, James D.; Flood, Kat; Fisch, Michael; Meindl, Richard S.; Eren, Metin I.
Abstract: Archaeologists have attributed the decline of North American utilitarian copper tools to changes in demography and social complexity during the Archaic to Woodland transition, ca. 3000 B.P. However, not all utilitarian copper tools disappeared: the copper awl persisted. Given that the copper tool types that disappeared, such as projectile points and knives, have been experimentally shown to be functionally inferior to their non-copper counterparts, we tested whether the copper awl persisted because it was functionally superior to those made of bone. Using replicated copper and bone awls in a controlled punching experiment that utilized an Instron Universal Materials Tester, we demonstrate that copper awls require significantly less force to punch through leather relative to bone awls. These results strongly support the hypothesis that tool function played an important role in the evolution of the North American copper tool repertoire 3000 B.P. Highlights: North American copper awls persisted over time while other copper tools did not. Replicated copper and bone awls were tested on an Instron Materials Tester. Force (N) measures show that copper awls are more energetically more efficient. Results suggest that copper awls persisted due to performance benefits.